FAKTOR PENDORONG INDONESIA MENJADIKAN SUSTAINABLE ENERGY TRANSITION SEBAGAI SALAH SATU ISU PRIORITAS DALAM PRESIDENSI G20 TAHUN 2022 - Sihombing, Ari Pranata; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Indonesia as the host in the G20 High Level Conference in Bali places Indonesia in a position as a mediator in the formulation of the problem and the cooperation that will be built by all G20 members. Of the many existing issues, Indonesia brought Sustainable Energy Transition to be one of the priority issues that will be discussed during the presidency this time. Factors and driving force of Indonesia so as to make the issue a priority issue the main focus in this study. In order to obtain more specific accuracy to the results of this study, researchers use the theory of green politics as a basic reference for this research. Green Politics Theory itself has the goal of through cooperation that is dujalu by countries whose nods are expected to create a balanced environment and prosperity for all living things. The results of this study will explain the factors and efforts made by Indonesia in realizing energy transitions through cooperation in the G20 forum. Indonesia is also expected to integrate the interests of developing countries in general and the interests of countries in Southeast Asia specifically. The role of Indonesia in every G20 Summit is to always advance the interests of developing countries and uphold the creation of an inclusive and sustainable global economic system. Through the Transitions Working Group (ETWG) Indonesia encourages energy transitions for all G20 members, namely through energy accessibility, increasing net energy, and increasing energy financing. Keywords: G20, ETWG, Green Politics, Organization, Sustainable Energy Transision